2009
DOI: 10.1105/tpc.108.063883
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between Cold Response and Flowering in Arabidopsis Is Mediated through the Flowering-Time Gene SOC1 and Its Upstream Negative Regulator FLC

Abstract: The appropriate timing of flowering is pivotal for reproductive success in plants; thus, it is not surprising that flowering is regulated by complex genetic networks that are fine-tuned by endogenous signals and environmental cues. The Arabidopsis thaliana flowering-time gene SUPPRESSOR OF OVEREXPRESSION OF CONSTANS1 (SOC1) encodes a MADS box transcription factor and is one of the key floral activators integrating multiple floral inductive pathways, namely, long-day, vernalization, autonomous, and gibberellin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
234
0
3

Year Published

2013
2013
2015
2015

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 237 publications
(251 citation statements)
references
References 61 publications
14
234
0
3
Order By: Relevance
“…During such cold periods, SOC1 expression is reduced and the concomitant delay in flowering correlates with an increase in the expression of cold-regulated genes such as C-REPEAT/DROUGHT-RESPONSIVE ELEMENT-BIND-ING FACTOR (CBF) and cold-response marker genes such as COLD-REGULATED15a (COR15a) and COR15b. Inversely, SOC1 overexpression results in the inverse regulation of cold-regulated genes, and this supports experimental data that indicate that SOC1 is a direct regulator of cold-regulated genes (Seo et al, 2009).…”
supporting
confidence: 86%
See 4 more Smart Citations
“…During such cold periods, SOC1 expression is reduced and the concomitant delay in flowering correlates with an increase in the expression of cold-regulated genes such as C-REPEAT/DROUGHT-RESPONSIVE ELEMENT-BIND-ING FACTOR (CBF) and cold-response marker genes such as COLD-REGULATED15a (COR15a) and COR15b. Inversely, SOC1 overexpression results in the inverse regulation of cold-regulated genes, and this supports experimental data that indicate that SOC1 is a direct regulator of cold-regulated genes (Seo et al, 2009).…”
supporting
confidence: 86%
“…Here, we observed a suppression of the increased cold tolerance of soc1 in the absence of GNC and GNL as well as an increase in cold tolerance when the two GATAs are overexpressed. It was proposed that the antagonistic regulation of cold tolerance and flowering time by SOC1 may be relevant during short periods of cold temperature as they can be experienced by plants during cold periods in spring (Seo et al, 2009). Two studies have recently reported the genome-wide identification of direct SOC1 targets using ChIP (Immink et al, 2012;Tao et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations